Wie mächtig sind Archive?/Perspektiven der Archivwissenschaft - Hering, Rainer (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2013)
In October 2011, the Representation of the State of Schleswig-Holstein to the Federal Government hosted the conference Power and Impotence of the Archives". Cultural and archival scholars, archivists and academics debated the mission and benefits, responsibility and performance of archives in a widely digitized knowledge society. Archival scholarship in Germany has so far not dealt in detail with the challenge posed by the understanding of the archive in the atmosphere of postmodernity by cultural scholars. With the symposium documented here, the long overdue examination of these positions will now begin. The discussion was conducted in a pragmatic and practice-oriented manner. The contributions combine archival research considerations with the presentation of selected individual topics from archival practice and archive history."